Hepadnaviral hepatocarcinogenesis: in situ visualization of viral antigens, cytoplasmic compartmentation, enzymic patterns, and cellular proliferation in preneoplastic hepatocellular lineages in woodchucks - Radaeva, Svetlana; Li, Yanhua; Hacker, Hans Jörg; Burger, Vera; Kopp-Schneider, Annette; Bannasch, Peter (Journal of hepatology, 2001)
Background/Aims: Hepadnaviral hepatocarcinogenesis induced in woodchucks with and without dietary aflatoxin B1 has been established as an appropriate …